The Role of NPM1 in the Invasion and Migration of Drug Resistant Bladder Cancer - Luo, Chenshuo; Lei, Ting; Zhao, Man; Meng, Qian; Zhang, Man (Urology Journal, 2021)
Purpose: To study the difference of tumor progression caused by differential expression of NPM1 in drug-resistant bladder cancer. Materials and Methods: The expression of NPM1 was analyzed by PCR and Western blot. NPM1 silencing bladder cancer cells (T24/DDP Lv-NPM1, PUMC-91/DDP Lv-NPM1) and overexpressing bladder cancer cells (T24/ DDP Lv5-NPM1, PUMC-91/DDP Lv5-NPM1) were established by lentivirus and limited dilution method. The efficiency of gene interference was detected by fluorescence microscopy and Western blot. The migration ability and invasion ability of tumor in vitro were analyzed by wound healing assay and transwell cell invasion test, and the tumorigenic ability in vivo was judged by nude mouse tumorigenicity assay. Results: Compared with the corresponding negative control group, both NPM1 silencing cell lines T24/DDP Lv-NPM1 and PUMC-91/DDP Lv-NPM1 showed strong migration ability and high invasive ability. At the same time, there was no significant difference in migration ability and the invasive cells proportion between NPM1 overexpressing cell line and related negative control group. NPM1 silencing bladder cancer cells had obvious tumorigenicity in vivo. Conclusion: NPM1 silencing cells had significant migration and invasion ability. The silencing of NPM1 will accelerate tumorigenicity of drug resistant bladder cancer. Differential expression of NPM1 is of great value in monitoring the progression of drug-resistant bladder cancer.